Procedures in the 1st year of life for children with trisomy 13 and trisomy 18, a 25‐year, single‐center review. Issue 3 (21st August 2016) - Josephsen, Justin B.; Armbrecht, Eric S.; Braddock, Stephen R.; Cibulskis, Catherine C.
Abstract : Care of the child born with trisomy 13 or 18 has evolved over the past few decades, leading to increased healthcare utilization. We hypothesized that there has been an increase in procedures across all intensity types, including major, invasive procedures. We performed a retrospective‐cohort study of children with trisomy 13 or 18 from 1990 to 2014 in a quaternary, free‐standing children's hospital. Children were identified using ICD‐9 billing diagnoses. Procedures were identified during these encounters and categorized by intensity (major, intermediate, or minor). One hundred thirty‐two children with trisomy 13 or 18 were identified. In children with trisomy 13, major procedures increased from period 1 (1990–1997) to period 3 (2006–2013) from 0.11 to 0.78 procedures per patient. For trisomy 18, the increase between the time periods was from 0.14 to 1.33 procedures per patient. By the end of the study period, nearly all trisomy 13 patients had a major procedure and the majority of those with trisomy 18 had undergone a major procedure. Estimated 1‐year survival for those with a major procedure was 30% and 22% for trisomies 13 and 18, respectively. In conclusion, there was an increasing rate of procedures per patient of all intensity levels over the 25‐year study period. Given differences in characteristics in those with trisomies 13 and 18, and effects of intervention on survival, an individualized approach to care of these patients should be employed by parents and healthcare providers, using factors such as trisomy type, infant gender, co‐morbidities, and parental preference. © 2016 Wiley Periodicals, Inc.